0.1(40)=0.4(70+p)-0.6p

Rewrite the equation as 0.4(70+p)-0.6p=0.1(40).

0.4(70+p)-0.6p=0.1(40)

Simplify each term.

Apply the distributive property.

0.4⋅70+0.4p-0.6p=0.1(40)

Multiply 0.4 by 70.

28+0.4p-0.6p=0.1(40)

28+0.4p-0.6p=0.1(40)

Subtract 0.6p from 0.4p.

28-0.2p=0.1(40)

28-0.2p=0.1(40)

Multiply 0.1 by 40.

28-0.2p=4

Subtract 28 from both sides of the equation.

-0.2p=4-28

Subtract 28 from 4.

-0.2p=-24

-0.2p=-24

Divide each term in -0.2p=-24 by -0.2.

-0.2p-0.2=-24-0.2

Cancel the common factor of -0.2.

p=-24-0.2

Divide -24 by -0.2.

p=120

p=120

Solve for p 0.1(40)=0.4(70+p)-0.6p